Dynamic programming for the control of power quality in inbalanced medium voltage networks with distributed generation - Piumetto, Miguel; Pucheta, Julián; Gómez Targarona, Juan Carlos (2022)
Fil: Piumetto, Miguel. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.